Referral pattern of neonates with severe respiratory failure for extracorporeal membrane oxygenation. Issue 2 (26th June 2007) - Tiruvoipati, R; Pandya, H; Manktelow, B; Smith, J; Dodkins, I; Elbourne, D; Field, D
Abstract : Background: Extracorporeal membrane oxygenation (ECMO) remains the mainstay of management in neonates with severe but potentially reversible respiratory failure. In the UK, ECMO is available only as a supraregional service at four centres. Objective: To explore regional variations in ECMO referrals and neonatal deaths due to severe respiratory failure in England, Wales and Northern Ireland. Methods: In this retrospective study, data regarding ECMO referrals due to neonatal respiratory failure from January to December 2002 were obtained from the four UK ECMO centres and then subdivided according to the Government Office Regions. Anonymised data regarding neonatal deaths was obtained from Confidential Enquiry into Maternal and Child Health. Neonatal deaths were classified into four groups (group 1: deaths potentially avoidable by ECMO; group 2: deaths where it was unclear whether ECMO would have been of benefit; group 3: neonates not eligible for ECMO; and group 4: data inadequate to classify deaths). Results: There was significant regional variation in the rates of both ECMO referral (0.10 to 0.46 per 1000 live births; (p<0.001)) and neonatal deaths (groups 1 and 2) (0.09 to 0.32 per 1000 live births; (p<0.001)). Regions with high referral rates for ECMO tended towards having higher group 1 plus group 2 neonatal death rates (correlation coefficient  = 0.75). Conclusion: It is possible that there are significant regional variations in the uptake of ECMO and in neonatal mortality due to severe respiratory failure. A confidential prospective study may further clarify these observations and identify the factors that might lead to these variations.